2012
DOI: 10.1016/j.ygcen.2012.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Individual variation in avian reproductive physiology does not reliably predict variation in laying date

Abstract: Experiments measuring temporal patterns of reproductive hormone concentrations or gonadal size under controlled conditions in response to a cue commonly assume that these proxies are indicative of the timing of egg laying. This assumption often remains untested, with few studies reporting both reproductive development and the onset of laying. We kept in total 144 pairs of great tits (Parus major) in separate climate-controlled aviaries over 4 years to correlate pre-breeding plasma luteinizing hormone (LH), pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 51 publications
1
40
0
Order By: Relevance
“…After collection, chicks were transferred to the Netherlands (Netherlands Institute of Ecology, NIOO-KNAW, Wageningen) and hand reared following basic protocols (e.g., Drent et al 2003, Reparaz et al 2014). Once they were adults, birds were settled in opposite-sex pairs in 36 climate-controlled chambers (2 3 The Auk: Ornithological Advances 135:218-227, Q 2018 American Ornithological Society 2 3 2.25 m; chamber walls made of white sandwich panels; one pair of birds per aviary; see also Visser et al 2009, Schaper et al 2012a, 2012b) under artificial light. Photoperiod was adjusted every day, and the main sources of light were 3 high-frequency, 36 W TL-tubes, which had different spectra in order to approach a natural range of wavelengths; 5 min before the TLs were switched on and 5 min after they were turned off, an 8 W light bulb mimicked dawn and dusk.…”
Section: Controlled-climate Chambers: Blue Titsmentioning
confidence: 99%
“…After collection, chicks were transferred to the Netherlands (Netherlands Institute of Ecology, NIOO-KNAW, Wageningen) and hand reared following basic protocols (e.g., Drent et al 2003, Reparaz et al 2014). Once they were adults, birds were settled in opposite-sex pairs in 36 climate-controlled chambers (2 3 The Auk: Ornithological Advances 135:218-227, Q 2018 American Ornithological Society 2 3 2.25 m; chamber walls made of white sandwich panels; one pair of birds per aviary; see also Visser et al 2009, Schaper et al 2012a, 2012b) under artificial light. Photoperiod was adjusted every day, and the main sources of light were 3 high-frequency, 36 W TL-tubes, which had different spectra in order to approach a natural range of wavelengths; 5 min before the TLs were switched on and 5 min after they were turned off, an 8 W light bulb mimicked dawn and dusk.…”
Section: Controlled-climate Chambers: Blue Titsmentioning
confidence: 99%
“…Some studies also failed to find any correlation between prolactin levels and LH levels (e.g. Small et al, 2007;Schaper et al, 2012;Ryan et al, 2014) suggesting that prolactin and LH levels or egg production may be uncoupled under some circumstances (such as in determinate layers that always lay the same clutch size). Because of this potential disconnection between prolactin levels and egg laying, other specific hormones could be involved and play a major role in clutch size determination (Rozenboim et al, 2004;Mobarkey et al, 2013).…”
Section: Prolactin Stress and Clutch Size Determinationmentioning
confidence: 99%
“…The temporal discrepancy found between the effects of light at night on reproductive physiology and laying date suggests that while reproductive physiology of temperate avian species is mostly modulated by light (Dawson et al 2001 ), and thus light pollution can have a stronger effect on it, laying date is a complex life history decision that is regulated not only by photoperiod, but also by factors that reflect more the current environmental conditions, such as temperature and food abundance (Caro et al 2013 ). A recent captive study on the relationship between gonadal growth and egg laying date has shown very weak correlation between the two variables, highlighting that these are independent mechanisms that can be differentially affected by artificial lights (Schaper et al 2012 ). It remains to be established how light at night affects reproductive timing.…”
Section: Light Pollution and Annual Cyclesmentioning
confidence: 99%